Implementasi Program Pemberdayaan Masyarakat di Kampung Perawang Barat KecamatanTualang Kabupaten Siak - Freddi S, Antonius (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article aims to describe the implementation of community empowerment programs carried out in Kampung Perawang Barat, Tualang District, Siak Regency. The main focus of this study is to explore how these programs contribute to improving the quality of life and well-being of the local community. The method used in this article is a qualitative descriptive approach through direct field observation. The findings indicate that several empowerment programs have been implemented, such as fishery product processing training, hydroponic farming training, health and environmental hygiene awareness campaigns, distribution of direct cash assistance (BLT), and raising awareness on the importance of paying Land and Building Tax (PBB). Each program has shown positive impacts in enhancing skills, food security, environmental awareness, economic welfare, and citizen participation in village development. The conclusion of this study shows that community empowerment in Kampung Perawang Barat has been effectively implemented through active citizen participation and cross-sector collaboration. The implementation of these programs proves that a participatory approach can foster community self-reliance and promote sustainable rural development. Keywords: Community Empowerment, Village Program, Citizen Participation, Welfare, and Sustainable Development